Subwavelength Field Shaping Approach Based on Time Reversal Technique and Defective Metasurfaces - Ren Wang; Jinpin Liu; Yanhe Lv; Zhipeng Wang; Sheng Liu; Moran Zhang; Shuai Ding; Bing-Zhong Wang (IEEE Access)
The resolution limitation is a main problem in the time-reversed field shaping system. In this paper, a subwavelength field shaping approach is proposed by combining time reversal (TR) technique and defective resonant metasurfaces. The subwavelength 2D and 3D field patterns can be effectively realized in both single-target and multi-target field-shaping systems. The resolution in both single-target and multi-target field-shaping systems aided with defective metasurfaces is approximately $0.1~λ $ , which is corresponding to the dimension of the applied metasurface cell. The proposed technique can be used for wireless power transfer, industrial heating, and localized wireless communications.